Uji Kualitas Mutu Material Batu Bata Provinsi Jambi - Gusni Vitri; Wiwin Putri Zayu; Muhammad Febri Andrean (GLOBAL SCIENTS PUBLISHER, 2025)
Bricks are one of the materials used for construction. Among the areas producing brick material in Jambi Province are Bungo Regency, Sarolangun Regency and East Tanjung Jabung. This research was conducted to determine the quality of bricks, both in terms of shape, strength and the materials from which they are made. The tests carried out are shape and size tests, compressive strength tests. Testing was carried out at the Materials Laboratory of the Padang Institute of Technology by randomly taking samples of bricks from manufacturing furnaces in 3 (three) regencies of Jambi Province, namely Bungo Regency, Sarolangun Regency and East Tanjung Jabung Regency. From the test results, recommendations will be made for good quality bricks for construction work and if low quality bricks are found, recommendations for improvements will be made for brick making kilns. The research results showed that the size of the test bricks from 3 (three) districts in Jambi Province did not meet the standard sizes of SNI 15-2094-2000. The average size is 116.67 mm long, 73.3 mm wide and 65 mm high. The brick compressive strength test results were only 3.25 N/mm2, which does not meet the minimum SNI 15-2094-2000 standard of 5 N/mm2. The brick making process is still very traditional without brick quality control.